The Implementation of Ta’zīr Punishment as an Educational Reinforcement in Islamic Law - Djalaluddin, Muhammad Mawardi; Mas'ud, Bulqia; Sumardi, Dedy; Bararah, Isnawardatul; Kamus, Kamus (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
This article aims to examine the application of ta’zīr punishment as a reinforcement of education in Islamic law. Humans are mulattoes or social beings who are related to one another, they cannot be separated from interactions with others. In order for this relationship to be in the corridor and frame of justice, Allah sent down rules in the form of orders and prohibitions. This study is a normative legal study using ushul fiqh theory and maslāhah theory. This study concludes that all commands and prohibitions contained in Islamic law are based on the Qur'an and the commands and prohibitions of the Prophet. which is formulated in fiqh, it will be seen that everything has a specific purpose, namely the benefit of mankind. If there is a violation of these rules, a penalty will be imposed, whether the punishment is in the form of ḥadd, qiṣaṣ or ta’zīr punishment. In addition to ḥadd, qiṣaṣ, kaffārah punishments, ta’zīr punishments are seen as punishments/sanctions that contain educational values because they aim to create a deterrent effect on the perpetrators and become a lesson for others not to commit similar violations. Therefore, this study argues that the imposition of punishment in Islamic law including ta’zīr contains beneficial values that educate humans and has a deterrent effect for perpetrators and for others.